Modern etiotropic therapy of chronic viral hepatitis B - E. B. Bun'kova; N. A. Bileva; A. E. Bilev; M. I. Sinel'nikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Chronic viral hepatitis B (CHB) is a significant global health problem. The biological characteristics of the hepatitis B virus, which causes this disease, significantly impede the achievement of complete virus elimination in most patients. In this regard, the rational choice of drugs and antiviral therapy regimens is crucial for increasing life expectancy and improving the quality of life in patients with CHB. The purpose of this literature review is to identify current approaches and trends in etiotropic therapy for CHB.Materials and methods. The review uses data published in domestic and foreign scientific journals, clinical guidelines, regulatory documents, and Internet resources.Results. Currently, the most effective means of etiotropic therapy for CHB are interferons (standard interferon alpha, pegylated interferons alpha-2a and alpha-2b), as well as first-line nucleoside/nucleotide analogs (entecavir, tenofovir) and second-line analogs (lamivudine, telbivudine, adefovir). The choice of a specific drug is determined by the patient's clinical condition, preferences, availability, and cost of treatment. Despite certain limitations of current etiotropic therapies for CHB, their use can significantly increase patients' life expectancy and improve their quality of life.